High-specific-energy battery adopting surface alloying lithium negative electrode and preparation method of high-specific-energy battery

Through the surface alloy lithium negative electrode method, the problems of lithium dendrites and side reactions during the lithium battery circulation process are solved, the cycle stability and safety of the battery are improved, and the preparation and industrial production of high-specific energy batteries are realized.

CN119208541APending Publication Date: 2024-12-27CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411276845.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the circulation process of lithium metal secondary batteries, the surface charge distribution is uneven, and the growth of lithium dendrites leads to battery short circuits and side reactions, which affects the reversibility and safety of battery cycles. The viscosity of lithium metal is poor, and the manufacturing controllability and cost are controlled. high.

Method used

Through the method of surface alloying lithium negative electrode, alloying elements are introduced to form a stable modification layer, inhibiting the generation and side reaction of lithium dendrites, and improving the strength of lithium metal. High-specific energy positive electrodes and ether electrolytes are used, combined with ceramic coated separators. High-specific energy flexible packaging lithium metal batteries are prepared by Z-shaped lamination.

Benefits of technology

It effectively improves the cycle stability and safety of lithium batteries, simplifies the manufacturing process, is suitable for large-scale production, and improves the specific energy density and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-specific-energy battery adopting a surface alloying lithium negative electrode and a preparation method of the high-specific-energy battery, a metal simple substance or a metal compound capable of reacting with a lithium foil is dissolved in an organic solvent to form a precursor solution, the precursor solution is sprayed on the surface of the lithium foil for standing and reacting for a period of time, redundant liquid is erased, the solvent is removed through drying, and the surface alloying lithium negative electrode is obtained. And preparing the high-specific-energy flexible package lithium metal battery by adopting a high-specific-energy positive electrode, an ether electrolyte, the surface alloyed lithium negative electrode and a ceramic coating diaphragm in a Z-shaped lamination manner. The surface alloying can promote the uniform deposition of lithium ions and inhibit the generation of lithium dendrites, the barrier formed by the modification layer can effectively prevent the side reaction between electrolyte and lithium metal and play a role in stabilizing an interface, and the high-specific-energy battery prepared from the modified lithium metal has higher cycling stability. The method is simple and feasible, is suitable for large-scale preparation, and provides a feasible way for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical power sources, and in particular relates to a high specific energy battery using a surface alloyed lithium negative electrode and a preparation method thereof. Background Art

[0002] Lithium metal has the advantages of light texture, good ductility, strong conductivity, etc. It has very active electrochemical properties, an electrode potential of -3.041V, and a theoretical specific capacity of up to 3860mAh / g, making it one of the metals with the highest mass energy density discovered so far. Replacing the intercalation negative electrode in lithium-ion batteries with lithium metal can greatly increase the energy density of energy storage batteries, and even obtain a battery system with a specific energy of ultra-high 750Wh / kg, expanding the application direction of secondary batteries.

[0003] However, the application of lithium metal secondary batteries still faces many problems: first, during the cycle of lithium metal, there will be an uneven surface charge distribution problem, which will produce lithium dendrites. The growth of lithium dendrites will pierce the diaphragm and cause battery short circuit, posing a safety hazard; second, interfacial side reactions, dendrites and other problems will lead to the large-scale production of "dead lithium", affecting the reversibility of battery cycles and causing a sharp drop in capacity; third, lithium metal is very active and will react quickly with air or water, resulting in more stringent battery preparation conditions, and thin layers of lithium metal are sticky, have poor strength, and are difficult to operate, resulting in increased manufacturing controllability and cost.

[0004] For the design of high-energy-density batteries, the reliability of lithium metal negative electrodes must be considered. Modifying lithium negative electrodes is the most direct and effective way to improve the performance of lithium metal batteries. The cycle performance of lithium negative electrodes mainly depends on whether uniform deposition of lithium can be achieved and its stability with the electrolyte. Through the modification of lithium metal surface alloying, elements that can induce uniform deposition of lithium can be introduced into the negative electrode surface. At the same time, the surface of the lithium negative electrode can be effectively protected, and side reactions with the electrolyte, ambient air and water can be inhibited. In addition, the alloying process will form a solid solution enhancement effect, which greatly improves the strength of thin-layer lithium metal, laying the foundation for industrial continuous production. On the basis of the treated lithium metal negative electrode, a high-energy-density positive electrode and an ether electrolyte that is stable with lithium metal are matched, and a high-energy-density battery system can be obtained through reasonable battery design. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a high-energy-density battery using a surface alloyed lithium negative electrode and a preparation method thereof, which can effectively inhibit the generation of lithium dendrites, prevent the occurrence of side reactions between the electrolyte and metallic lithium, and play a role in stabilizing the interface, thereby achieving performance improvement of the high-energy-density lithium battery.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high-energy-density battery using a surface-alloyed lithium negative electrode, using a high-energy-density positive electrode, an ether electrolyte, a surface-alloyed lithium negative electrode, and a ceramic coating separator, and preparing a high-energy-density soft-package lithium metal battery by a Z-shaped stacking method, wherein the preparation method of the surface-alloyed lithium negative electrode is: dissolving a metal element or a metal compound that can react with lithium foil in an organic solvent to form a precursor solution, spraying the precursor solution on the surface of the lithium foil and letting it stand, after a period of reaction, wiping off excess liquid, drying and removing the solvent, and obtaining a metal lithium negative electrode with an alloying modification layer on the surface.

[0007] The environmental humidity of the above reaction is 0.1%-1%, the reaction temperature is 0°C-40°C, the reaction time is 2 minutes-2 hours, and the drying temperature is 20°C-80°C.

[0008] Preferably, the alloying modification layer has a thickness of 100 nm-1 μm.

[0009] Preferably, the molar ratio of the alloying element to the lithium element in the alloying modification layer is 1:1-1:6.

[0010] Furthermore, the metal element or metal compound is one or more combinations of lithium nitrate, lithium nitrite, ammonium nitrate, sodium nitrate, potassium nitrate, triethylamine trihydrofluoride, pyridine hydrofluoride, melamine hydrofluoride, tetra-n-butylammonium difluoride hydrofluoride, tetraethylammonium fluoride tetrahydrofluoride, N,N-diisopropylethylamine trihydrofluoride, silver nanowires, graphene quantum dots, and zinc nanowires.

[0011] Furthermore, the organic solvent is one or more combinations of tetrahydrofuran, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, acetonitrile, isopropyl ether, acetone, butanone, isopropanol, butanol, hexane, cyclohexane, N-dimethylacetamide, N-methyl-2-pyrrolidone, benzene, toluene, dimethyl sulfoxide, carbon tetrachloride, trichloroethylene, and pyrrole.

[0012] Furthermore, the high specific energy is layered LiCoO2, LiNiO2 and LiNi x Co 1-x O2, ternary LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 and LiNi 0.85 Co 0.1 Al 0.05 O2, LiNi 0.95 Co 0.02 Mn 0.03 O2, spinel LiMn2O4, 5V spinel LiNi 0.5 Mn 1.5O4, phosphate LiMPO4 where M = Fe, Mn, lithium-rich manganese-based positive electrode material Li[Li x (MnM) 1-x ]O2 where M = Ni, Co, Fe, sulfur cathode, air cathode, manganese oxide, vanadium oxide, chromium oxide and carbon fluoride.

[0013] Furthermore, the ceramic components in the ceramic coating diaphragm are aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), lithium lanthanum zirconium oxide (Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ) and the coating thickness is 0.5-2μm.

[0014] Furthermore, the ether electrolyte includes a lithium salt and a solvent, wherein the lithium salt is one or more of lithium bis(trifluoromethylsulfonate)imide, lithium bis(fluorosulfonyl)imide, and lithium perchlorate, and the solvent is one or more of ethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,2-di(cyanoethoxy)ethane, 18-crown ether-6, diphenyl ether, 1,2-dimethoxypropane (DMP), and dimethoxymethane (DMM) that have a strong solubility for the lithium salt and can form a stable chelate, and the concentration of the lithium salt is 2.5 mol / L-6 mol / L.

[0015] The high specific energy battery using a surface alloyed lithium negative electrode is prepared by the preparation method.

[0016] The beneficial effects of the present invention are as follows: the present invention forms a stable lithium negative electrode through alloying treatment on the surface of metallic lithium, thereby being able to solve the problems of poor cycle stability and potential safety hazards caused by lithium dendrite growth and interface side reactions during the cycle of lithium metal batteries, and at the same time being able to solve the problem of poor processability of the lithium metal negative electrode. On this basis, a high-energy-density battery is prepared, which can effectively improve the battery cycle stability and lay the foundation for the practical application of lithium metal batteries. The method is simple and easy to implement and is conducive to large-scale production. DETAILED DESCRIPTION

[0017] In order to further understand the content, features and effects of the present invention, the following embodiments are given and described in detail as follows:

[0018] The present invention adopts a high specific energy battery with a surface alloyed lithium negative electrode, which is prepared according to the following steps:

[0019] To prepare a surface alloyed lithium negative electrode, a metal element or metal compound that can react with lithium foil is dissolved in an organic solvent to form a precursor solution, and the precursor solution is sprayed on the surface of the lithium foil and allowed to stand and react for a period of time, and then the excess liquid is wiped off and the solvent is dried to obtain a metal lithium negative electrode with an alloying modification layer on the surface. The ambient humidity is 0.1%-1%, the reaction temperature is 0℃-40℃, the reaction time is 2 minutes-2 hours, and the drying temperature is 20℃-80℃. The thickness of the alloying modification layer is 100nm-1μm. The molar ratio of the alloying element to the lithium element in the alloying modification layer is 1:1-1:6. Among them, the metal element or metal compound is one or more combinations of lithium nitrate, lithium nitrite, ammonium nitrate, sodium nitrate, potassium nitrate, triethylamine trihydrofluoride, pyridine hydrofluoride, melamine hydrofluoride, tetra-n-butylammonium difluoride hydrofluoride, tetraethylammonium fluoride tetrahydrofluoride, N,N-diisopropylethylamine trihydrofluoride, silver nanowires, graphene quantum dots, and zinc nanowires.

[0020] The above-mentioned organic solvent includes one or more combinations of tetrahydrofuran, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, acetonitrile, isopropyl ether, acetone, butanone, isopropanol, butanol, hexane, cyclohexane, N-dimethylacetamide, N-methyl-2-pyrrolidone, benzene, toluene, dimethyl sulfoxide, carbon tetrachloride, trichloroethylene, and pyrrole.

[0021] The above high specific energy is layered LiCoO2, LiNiO2 and LiNi x Co 1-x O2, ternary LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 and LiNi 0.85 Co 0.1 Al 0.05 O2, LiNi 0.95 Co 0.02 Mn 0.03 O2, spinel LiMn2O4, 5V spinel LiNi 0.5 Mn 1.5 O4, phosphate LiMPO4 where M = Fe, Mn, lithium-rich manganese-based positive electrode material Li[Li x (MnM) 1-x ]O2 where M = Ni, Co, Fe, sulfur cathode, air cathode, manganese oxide, vanadium oxide, chromium oxide and carbon fluoride.

[0022] High-energy-density batteries use surface alloyed lithium negative electrodes, ceramic coating separators, and high-energy-density positive electrodes to prepare high-energy-density soft-package lithium metal battery cells through Z-shaped stacking. Ether electrolytes are injected and left to stand for 24 hours before formation, exhaust and secondary sealing, and then performance testing.

[0023] The ceramic components of the ceramic coating diaphragm are aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), lithium lanthanum zirconium oxide (Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ) or one or more combinations thereof. The coating thickness is 0.5-2 μm.

[0024] The above-mentioned ether electrolyte includes a lithium salt and a solvent, wherein the lithium salt is one or more of lithium bis(trifluoromethylsulfonate)imide, lithium bis(fluorosulfonyl)imide, and lithium perchlorate. The solvent is one or more of ethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,2-di(cyanoethoxy)ethane, 18-crown ether-6, diphenyl ether, 1,2-dimethoxypropane (DMP), and dimethoxymethane (DMM) that have strong solubility for lithium salts and can form stable chelates. The concentration of the lithium salt is 2.5 mol / L-6 mol / L.

[0025] Example 1

[0026] (1) Preparation of surface alloyed lithium anode

[0027] In a dry room with an ambient humidity of 0.5%, a 0.1 mol / L lithium nitrate tetrahydrofuran solution was sprayed on the surface of lithium foil for 1 hour at a reaction temperature of 30°C. After that, the excess liquid on the surface was wiped off and then vacuum dried at 60°C for 8 hours to obtain a metal lithium negative electrode with a surface nitrogen alloying modification layer. The modification layer thickness was 1 micron and the molar ratio of nitrogen to lithium in the modification layer was 1:3. Symmetrical batteries were assembled using surface alloyed lithium metal as electrodes. At room temperature, the current was 1 mA / cm 2 Current density and 4mAh / cm 2 The surface capacity is circulated.

[0028] (2) Preparation of high specific energy batteries

[0029] In a dry room with an ambient humidity of 0.5%, the modified metal lithium was used as the negative electrode, LiNi 0.95 Co 0.02 Mn 0.03 O2 was used as the positive electrode, matched with a ceramic coating diaphragm, and a soft-pack battery was prepared by Z-shaped stacking. A high-concentration salt ether electrolyte with a LiFSI lithium salt concentration of 3 mol / L was introduced. After formation, the test was carried out at a temperature of 25°C and a current of 1.2A. The voltage range of the specific energy test was 1.7V-4.4V, and the voltage range of the cycle test was 3.0-4.4V.

[0030] Example 2

[0031] (1) Preparation of surface alloyed lithium anode

[0032] In a dry room with an ambient humidity of 0.5%, a dimethyl carbonate solution containing silver nanowires was sprayed on the surface of lithium foil at a concentration of 0.1 mol / L. The reaction was carried out for 0.5 h at a reaction temperature of 35 °C. The excess liquid on the surface was then wiped off and vacuum dried at 70 °C for 6 h. A metallic lithium negative electrode with a silver alloying modification layer on the surface was obtained. The modification layer thickness was 0.5 microns and the molar ratio of silver to lithium in the modification layer was 1:2. Symmetrical batteries were assembled using the surface alloyed lithium metal as electrodes. At room temperature, the current was 1 mA / cm 2 Current density and 4mAh / cm 2 The surface capacity is circulated.

[0033] (2) Step (2) Refer to step (2) of Example 1

[0034] Example 3

[0035] (1) Preparation of surface alloyed lithium anode

[0036] In a dry room with an ambient humidity of 0.5%, an isopropyl ether solution containing graphene quantum dots was sprayed on the surface of lithium foil at a concentration of 0.05 mol / L. The reaction was carried out for 2 hours at a reaction temperature of 30°C. After that, the excess liquid on the surface was wiped off and then vacuum dried at 60°C for 6 hours. A metal lithium negative electrode with a graphene alloying modification layer on the surface was obtained. The modification layer thickness was 0.8 microns and the molar ratio of carbon to lithium in the modification layer was 1:6. Symmetric batteries were assembled using surface alloyed lithium metal as electrodes. At room temperature, the current was 1 mA / cm 2 Current density and 4mAh / cm 2 The surface capacity is circulated.

[0037] Step (2) Refer to step (2) of Example 1

[0038] Comparative Example

[0039] Using pure lithium as the electrode, a symmetrical battery was assembled, and at room temperature, the current was 1 mA / cm 2 Current density and 4mAh / cm 2 The surface capacity is circulated.

[0040] In a dry room with an ambient humidity of 0.5%, pure metallic lithium was used as the negative electrode, LiNi 0.95 Co 0.02 Mn 0.03O2 is used as the positive electrode, matched with a ceramic coating diaphragm, and a soft-pack battery is prepared by Z-shaped stacking. A high-concentration salt (LiFSI) ether electrolyte is introduced and tested after formation. The test temperature is 25°C, the current is 1.2A, the voltage range of the specific energy test is 1.7V-4.4V, and the voltage range of the cycle test is 3.0-4.4V.

[0041] Table 1 is a comparison of the symmetrical battery performance of the surface alloyed lithium negative electrode in Examples 1 to 3 of the present invention and the pure lithium negative electrode in the comparative example, and their corresponding high specific energy battery performance.

[0042] Table 1

[0043] Symmetrical battery cycle time (h) 50 cycles capacity retention Example 1 920 93.4% Example 2 970 92.5% Example 3 1035 93.7% Comparative Example 436 70.3%

[0044] The symmetrical battery characterized the lithium dissolution-deposition stability of the lithium negative electrode. Under high current density and surface capacity, the cycle life of the surface alloyed negative electrode is 1 times that of pure lithium. The comparison results of the capacity retention rate of high-energy-density batteries after 50 cycles showed that the high-energy-density battery using a surface alloyed lithium negative electrode has better cycle stability, with a capacity retention rate of more than 90% after 50 cycles, while that of a pure lithium negative electrode battery is only 70%.

[0045] The negative electrode of lithium metal battery is the basis for obtaining high specific energy, stable cycle and improved safety. The method of lithium metal surface treatment can simply and effectively obtain high-performance negative electrode, which can be introduced into the battery system to obtain high specific energy while improving cycle life and safety. The present invention uses alloy element precursors to treat lithium metal, and in situ generates an alloying modification layer on its surface with a stable structure and capable of inducing uniform deposition of lithium, including but not limited to alloy components such as nitrogen, silver, carbon and zinc, effectively inhibiting the generation of lithium dendrites, preventing the occurrence of side reactions between electrolyte and metallic lithium, and playing a role in stabilizing the interface, thereby realizing the construction and performance improvement of high specific energy lithium batteries.

[0046] The present invention introduces alloying components on the surface of lithium metal through in-situ reaction to generate a modified layer with a stable structure, which can promote the uniform deposition of lithium ions and inhibit the generation of lithium dendrites. The barrier formed by the modified layer can effectively prevent the side reaction between the electrolyte and the lithium metal, play a role in stabilizing the interface, and the high specific energy battery prepared based on the modified lithium metal has higher cycle stability. This method is simple and easy to implement, suitable for large-scale preparation, and provides a practical way for industrial production. It can be applied to the field of unmanned aerial vehicles that have higher requirements for the endurance of energy storage batteries.

[0047] The embodiments described above are only used to illustrate the technical ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. The patent scope of the present invention cannot be limited only by this embodiment, that is, any equivalent changes or modifications made to the spirit disclosed by the present invention still fall within the patent scope of the present invention.

Claims

1. A method for preparing a high specific energy battery using a surface alloyed lithium negative electrode, characterized in that: A high-energy-density soft-package lithium metal battery is prepared by a Z-shaped stacking method using a high-energy-density positive electrode, an ether electrolyte, a surface alloyed lithium negative electrode, and a ceramic coating separator. The preparation method of the surface alloyed lithium negative electrode is as follows: a metal element or a metal compound that can react with lithium foil is dissolved in an organic solvent to form a precursor solution, the precursor solution is sprayed on the surface of the lithium foil and allowed to stand, and after a period of reaction, excess liquid is wiped off, and the solvent is removed by drying to obtain a metal lithium negative electrode with an alloying modification layer on the surface.

2. The method for preparing a high specific energy battery using a surface alloyed lithium negative electrode according to claim 1, characterized in that: The reaction environment humidity is 0.1%-1%, the reaction temperature is 0°C-40°C, the reaction time is 2 minutes-2 hours, and the drying temperature is 20°C-80°C.

3. The method for preparing a high specific energy battery using a surface alloyed lithium negative electrode according to claim 1, characterized in that: The thickness of the alloying modification layer is 100nm-1μm, and the molar ratio of the alloying element to the lithium element in the alloying modification layer is 1:1-1:

6.

4. The method for preparing a high specific energy battery using a surface alloyed lithium negative electrode according to claim 1, characterized in that: The metal element or metal compound is one or a combination of lithium nitrate, lithium nitrite, ammonium nitrate, sodium nitrate, potassium nitrate, triethylamine trihydrofluoride, pyridine hydrofluoride, melamine hydrofluoride, tetra-n-butylammonium difluoride hydrofluoride, tetraethylammonium fluoride tetrahydrofluoride, N,N-diisopropylethylamine trihydrofluoride, silver nanowires, graphene quantum dots, and zinc nanowires.

5. The method for preparing a high specific energy battery using a surface alloyed lithium negative electrode according to claim 1, characterized in that: The organic solvent is one or more combinations of tetrahydrofuran, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, acetonitrile, isopropyl ether, acetone, butanone, isopropanol, butanol, hexane, cyclohexane, N-dimethylacetamide, N-methyl-2-pyrrolidone, benzene, toluene, dimethyl sulfoxide, carbon tetrachloride, trichloroethylene, and pyrrole.

6. The method for preparing a high specific energy battery using a surface alloyed lithium negative electrode according to claim 1, characterized in that: The high specific energy is layered LiCoO2, LiNiO2 and LiNi x Co 1-x O2, ternary LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 and LiNi 0.85 Co 0.1 Al 0.05 O2, LiNi 0.95 Co 0.02 Mn 0.03 O2, spinel LiMn2O4, 5V spinel LiNi 0.5 Mn 1.5 O4, phosphate LiMPO4 where M = Fe, Mn, lithium-rich manganese-based positive electrode material Li[Li x (MnM) 1-x ]O2 where M = Ni, Co, Fe, sulfur cathode, air cathode, manganese oxide, vanadium oxide, chromium oxide and carbon fluoride.

7. The method for preparing a high specific energy battery using a surface alloyed lithium negative electrode according to claim 1, characterized in that: The ceramic components in the ceramic coating diaphragm are aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), lithium lanthanum zirconium oxide (Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ) and the coating thickness is 0.5-2μm.

8. The method for preparing a high specific energy battery using a surface alloyed lithium negative electrode according to claim 1, characterized in that: The ether electrolyte includes a lithium salt and a solvent, wherein the lithium salt is one or more of lithium bis(trifluoromethylsulfonate)imide, lithium bis(fluorosulfonyl)imide, and lithium perchlorate; the solvent is one or more of ethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,2-di(cyanoethoxy)ethane, 18-crown-6, diphenyl ether, 1,2-dimethoxypropane (DMP), and dimethoxymethane (DMM) that have a strong solubility for the lithium salt and can form a stable chelate; and the concentration of the lithium salt is 2.5 mol / L-6 mol / L.

9. A high specific energy battery using a surface alloyed lithium negative electrode prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Cited By

  • Lithium metal surface coating modification preparation process for sulfide solid electrolyte

    CN122091776A

  • A lithium metal surface coating modification preparation process for sulfide solid-state electrolyte

    CN122091776B